Enhancement of prefrontal functional connectivity under the influence of concurrent physical load during mental tasks - Shan Cheng; Lin Cong; Duoduo Hui; Chaolin Teng; Wenbin Li; Jin Ma (Frontiers in Human Neuroscience)
BackgroundsFunctional near-infrared spectroscopy (fNIRS) is widely used for the evaluation of mental workload (MWL), but it is not yet clear whether it is affected by physical factors during cognitive tasks. Therefore, the combined effects of physical and cognitive loads on hemodynamic features in the prefrontal cortex were evaluated.MethodsThirty-three eligible healthy male subjects were asked to perform three types of cognitive tasks (1-back, 2-back and 3-back). Concurrently, isotonic contraction aerobic exercise of the left upper limb was added. During this compound task, fNIRS signals, workload perception and task performance were recorded. Based on the oxyhemoglobin concentration, Pearson’s correlation coefficient (CORR), coherence value (COH) and the phase-locking value (PLV) were calculated to reflect FC among eight channels.ResultsOn the basis of effects of cognitive tasks, the concurrent physical activities would further increase National Aeronautics and Space Administration Task Load Index score (p < 0.05) and decrease task performance (p < 0.05). The fNIRS-based results showed that cognitive and physical loads had significant interaction effects on CORR (p < 0.05), COH (p < 0.05), and PLV (p = 0.010), while their main effects were not significant. The results of different channel pairs suggested that the functional connectivity between the right dorsolateral prefrontal cortex and the bilateral orbital frontal cortex was significantly enhanced under the combined effects of high physical and high cognitive load.DiscussionFrom the perspective of prefrontal functional connectivity, this study supports measurable effects of physical factor on operators’ mental load. The results provide a reference for the real-time (or online) assessment of the MWL level in the natural environment.